One-step synthesis and XPS investigations of chiral NHC–Au(0)/Au(i) nanoparticles. Issue 17 (15th April 2019) - Young, Adam J.; Sauer, Markus; Rubio, Guilherme M. D. M.; Sato, Akiko; Foelske, Annette; Serpell, Christopher J.; Chin, Jia Min; Reithofer, Michael R.
Abstract : NHC-AuNPs prepared via chlorido(1, 3-dimethyl- N -Boc- O -methylhistidin-2-ylidene)gold(i ), an NHC–Au(i ) complex, affords AuNPs containing not just Au(0), but also Au(i ). Abstract : Although N-heterocyclic carbenes (NHCs) have been demonstrated as suitable ligands for the stabilisation of gold nanoparticles (AuNPs) through a variety of methods, the manner in which such AuNPs form is yet to be fully elucidated. We report a simple and fast one-step synthesis of uniform chiral (l /d )-histidin-2-ylidene stabilised gold nanoparticles using the organometallic Au(i ) complex as a well defined starting material. The resulting nanoparticles have an average size of 2.35 ± 0.43 nm for the L analog whereas an average size of 2.25 ± 0.39 nm was found for the D analog. X-ray photoelectron spectroscopy analyses reveal the presence of Au(i ) and Au(0) in all NHC stabilised AuNPs. In contrast, measured X-ray photoelectron spectra of dodecanethiol protected gold nanoparticles showed only the presence of a Au(0) species. This observation leads us to postulate that AuNPs synthesised from organometallic NHC–Au(i ) complexes exhibit a monolayer of Au(i ) surrounding a Au(0) core. This work highlights the importance of synthetic method choice for NHC-stabilized AuNPs, as this could determine Au oxidation states and resulting AuNP properties such as catalytic activities and stabilities.